An observational study of simultaneous pulse oximetry and arterial oxygen saturation readings in intensive care unit/high dependency unit in COVID-19 patients - Rose, Nadia; Sriram, Ramya B; G S, Karthik; M J, Sowmya; Sudheer R (Asian Journal of Medical Sciences, 2022)
Background: The coronavirus-2019 (COVID-19) pandemic has increased the use of pulse oximeters worldwide. It has become an inevitable tool in the monitoring of the disease. However, the accuracy of pulse oximeters in COVID-19 has not been established. Aims and Objectives: The aims of the study were to examine the relationship between oxygen saturation as measured by pulse oximeter (SpO2) and oxygen saturation measured by arterial blood gas analysis (SaO2) measurements in COVID-19 patients admitted to the intensive care unit (ICU)/high dependency unit (HDU) and to assess the ability of SpO2 readings to detect low SaO2 and low oxygen tension in COVID-19 patients. Materials and Methods: This prospective observational study was conducted in the COVID-19 ICU and high dependency unit of a tertiary care hospital in Bengaluru, India. All patients admitted with confirmed COVID-19, meeting the eligibility criteria, were included in the study. We assessed bias and limits of agreement between paired samples of oxygen saturation from pulse oximetry (SpO2) and arterial oxygen saturation from blood gas analysis (SaO2). Results: The sample mean difference SpO2-SaO2 is −0.86% (bias) and the 95% confidence interval for the mean difference was −1.67 and −0.04. The lower limit of agreement was −7.32 with a 95% confidence interval (−8.74, −5.91). The upper limit of agreement was 5.61 with a 95% confidence interval of 4.19 and 7.02. Conclusion: SpO2 values are not completely dependable in estimating SaO2 in COVID-19 patients in ICU/HDU; therefore, arterial blood gas analysis measurement of oxygen saturation has to be done depending on the clinical scenario CTRI (CTRI/2020/11/029035).